2018
DOI: 10.1016/j.engstruct.2018.04.079
|View full text |Cite
|
Sign up to set email alerts
|

Direct displacement-based seismic design of flexible-base structures subjected to pulse-like ground motions

Abstract: In this paper, a practical displacement-based framework is presented for seismic design of flexible-base structures in near-fault regions. Particular attention is given to pulse-like motions that may cause significant damage to building structures. The proposed design methodology utilises displacement response spectra constructed using a new procedure, which takes into account the effect of pulse period. An equivalent fixed-base single-degree-of-freedom oscillator is adopted to capture the salient features of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…It is shown that a 0 parameter has the most significant effect on the seismic performance of a soil‐structure system . In conventional building practice, a 0 takes the value between 0 and 3 for fixed‐base structures to those with severe SSI effects The building Aspect ratio defined as trueH¯/r, which is usually considered as the second interacting parameter …”
Section: Details Of Structure Foundation and Soil Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that a 0 parameter has the most significant effect on the seismic performance of a soil‐structure system . In conventional building practice, a 0 takes the value between 0 and 3 for fixed‐base structures to those with severe SSI effects The building Aspect ratio defined as trueH¯/r, which is usually considered as the second interacting parameter …”
Section: Details Of Structure Foundation and Soil Conditionmentioning
confidence: 99%
“…For example, Ganjavi and Hao and Ganjavi et al conducted an extensive parametric nonlinear dynamic analysis to achieve near optimum seismic design solutions for SSI multistory shear buildings using the concept of uniform distribution of damage. In another relevant study, Lu et al investigated the seismic response of multistory shear such as structures considering SSI effects using a wide range of design parameters. Based on the results of their study, they developed an improved SSI replacement model and proposed a practical site and interaction‐dependent performance‐based seismic design methodology for flexible‐base structures.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, both frame and shear wall systems have their own displacement ductility and equivalent viscous damping. The displacement ductility of the shear wall can be calculated by Equation (12), whereas for the equivalent viscous damping of the shear wall can be calculated using Equation (13) [13].…”
Section: ) Ddbd Concept For Dual Systemmentioning
confidence: 99%
“…This design shear force and flexibility of the structure always link to each other. Meanwhile, in the performance-based design, to predict the design shear forces of the structure during the earthquake in order to achieve the expected structural performance, further calculation using the Direct Displacement Method might be necessary [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…Tzimas et al studied collapse risk and residual drift performance of steel buildings equipped with post-tensioned moment-resisting frames and viscous damper in near-fault regions [23]. Number of recent studies investigated effects of near-fault strong ground motions on seismic-induced demand [24,25], seismic design code [26] and direct displacement-based design methodology [27]. According to the mentioned researches regarding fragility assessment of structures against near-fault strong ground motions, they give emphasis to the collapse limit state.…”
Section: Introductionmentioning
confidence: 99%